A comparative study between two systems with and without awareness in controlling HIV/AIDS - Saha, Shubhankar; Roy, Priti Kumar (Zielona Góra: Uniwersytet Zielonogórski)
It has always been a priority for all nations to reduce new HIV infections by implementing a comprehensive HIV prevention programme at a sufficient scale. Recently, the "HIV counselling & testing" (HCT) campaign is gaining public attention, where HIV patients are identified through screening and immediately sent under a course of antiretroviral treatment (ART), neglecting the time extent they have been infected.
Keywords: epidemic model; HIV/AIDS; awareness; anti-retroviral therapy; basic reproductive number; numerical simulation